(untitled) (Technological Innovations Journal, 2022)
The purpose of the research was to examine the development of the mathematical logical reasoning of the students of the first cycle of the Professional School of Initial Education of the National University of the Altiplano (Peru, period 2020). The research approach is quantitative, the type of research is descriptive, the design being transectional descriptive; the study sample consisted of 44 female students, selected by non-probabilistic sampling. The instrument used was the mathematical logical reasoning test, which consists of 20 items and was applied in a single act to the research subjects. The result achieved shows that 72% of them were able to conveniently develop mathematical logical reasoning, which evidenced that the use of specific skills and abilities allowed them to identify, relate, and adequately operate the necessary bases in solving problem situations. It is concluded that, based on the findings found, the majority of those evaluated managed to develop mathematical logical reasoning expressed in the arithmetic, algebraic, geometric and logical dimensions.